2017
DOI: 10.1016/j.bmcl.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole C-region analogues of 2-(3-fluoro-4-methylsulfonylaminophenyl)propanamides as potent TRPV1 antagonists

Abstract: A series of 1-substituted 3-(t-butyl/trifluoromethyl)pyrazole C-region analogues of 2-(3-fluoro-4-methylsulfonamidophenyl)propanamides were investigated for hTRPV1 antagonism. The structure activity relationship indicated that the 3-chlorophenyl group at the 1-position of pyrazole was the optimized hydrophobic group for antagonistic potency and the activity was stereospecific to the S-configuration, providing exceptionally potent antagonists 13S and 16S with K=0.1nM. Particularly significant, 13S exhibited ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The K i values for antagonism take into account the competition between capsaicin and the antagonist. 19 To evaluate the antagonistic potency of the compounds in Tables 2 and 3 for hTRPV1, assays were conducted using a fluorometric imaging plate reader (FLIPR) with hTRPV1 heterologously expressed in recombinant human embryonic kidney (HEK) cells. 15 The antagonistic activity was measured by inhibition of TRPV1 activation by capsaicin (10 nM) and was compared to that of the prototype antagonist, BCTC (K i(CAP) = 2.5 nM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The K i values for antagonism take into account the competition between capsaicin and the antagonist. 19 To evaluate the antagonistic potency of the compounds in Tables 2 and 3 for hTRPV1, assays were conducted using a fluorometric imaging plate reader (FLIPR) with hTRPV1 heterologously expressed in recombinant human embryonic kidney (HEK) cells. 15 The antagonistic activity was measured by inhibition of TRPV1 activation by capsaicin (10 nM) and was compared to that of the prototype antagonist, BCTC (K i(CAP) = 2.5 nM).…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of 1-oxo-1,2-dihydroisoquinolin-5-yl Aregion analogues (Scheme 2), 1-chloroisoquinoline was hydrolyzed to the corresponding 2-pyridone and then nitrated to give 5-nitro isoquinolin-1-one 16. The nitro reduction or Nmethylation followed by reduction of 16 afforded 17 and 18, respectively, which were converted to the final ureas (3,19) by employing the same route as discussed above. For the synthesis of the 1-oxo-1,2-dihydroisoquinolin-8-yl A-region analogue (Scheme 2), isoquinoline was brominated and then selectively nitrated to give 8-nitro isoquinoline 21.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much better results were achieved by reduction with the BH 3 *THF complex, but this reagent is expensive and can hardly be used in large-scale syntheses. LAH itself was used for the reduction of nonfluorinated pyrazolic nitriles to amines . We found that LAH reduction usually gave impure products with our substrates, and a laborious separation procedure was necessary.…”
Section: How Can Incidents Of This Kind Be Prevented?mentioning
confidence: 99%